PTH-147 Audit of an In-Patient Teaching Hospital Gastroenterology Workload in 2012. (4th June 2013) - Maxwell, H; Smart, C; Hamlin, P J
Abstract : Introduction: The aim of this retrospective study was to evaluate the patient demographics, route of admission, main diagnosis, duration of stay and quality of discharge summaries on the two 25 bedded gastroenterology wards at Leeds teaching hospitals NHS trust (LTHT) over a two month period. LTHT is a tertiary referral GI unit with 9 WTE consultants covering a population of 800, 000. Leeds has one of six UK liver transplant units but non-transplant hepatology is covered by general gastroenterology. Methods: Patients admitted over a 2 month period on the two designated gastroenterology wards were identified from ward registers of admission. Information regarding age, gender, route of admission, main diagnosis, duration of stay and quality of the discharge summary were recorded. Results: 362 patients were identified (123 (55%) male, mean age of 54 (range of 17 to 96)). Routes of admission were 254 (70%) from the emergency department or surgical assessment unit, 43 (12%) day cases, 18 (5%) elective admissions, 18 (5%) transferred from other specialities, 15 (4%) from clinic, 7 (2%) from endoscopy and 7 (2%) unclear. The main diagnoses are listed in table 1. There were 13 deaths (4% mortality). 305 patients (91%) had discharge summaries of which 290 (95%) were completed on time. Patients who died or were transferred to other specialities were not included. Conclusion: These data demonstrate the caseload mix admitted to a tertiary referral GI unit. 25% of admissions were for liver disease in addition to the service provided by the transplant unit. This reflects the national problem of the increasing burden of liver disease to the NHS. Understanding the case mix facilitates service development in line with the population needs and BSG recommendations such as alcohol teams, GI bleeding rotas and the IBD service standards. A significant proportion of miscellaneous admissions were for day case infusions which may be more appropriately delivered away from the acute bed base. The unit is striving for 100% timely and fully complete eDANs. Disclosure of Interest: None Declared.